Flashpoint [large type] - Coulter, Catherine (Coulter, Catherine. FBI thrillers, 2024)
"Agents Savich and Sherlock are back in the latest installment in Catherine Coulter's #1 New York Times bestselling FBI Thriller series, where the past refuses to stay buried. A year has passed since Elizabeth Palmer was nearly killed with hundreds more in the attempted bombing of St. Paul's in London, believed to be a terrorist act until the police discovered it was a cover for something even more sinister. For Elizabeth, life is finally back to normal. She's optimistic, her painting is getting accolades, when suddenly her world changes in a flash. With three new attempts on her life, and her connection to the terrorist attack, MI-5 gets involved to find out who is trying to kill her and why. Autumn Backman, twelve years old, begrudgingly accepts a summer job to shepherd Tash Navarro, a shy, bullied little boy. He's staying with his uncle while his father and stepmother go on a honeymoon in Europe. Then the unexpected happens. Autumn learns Tash is gifted psychically, like her, and Tash's father, Archer Navarro, is suspected of embezzling from his own firm. The FBI and Interpol are on the case, but Archer and his new wife have disappeared. Tash is scared and convinced his father needs help, so Autumn reaches out to Dillon Savich, the only person she knows who can find them. Desperate for answers, Elizabeth flies to Washington, D.C., to seek out Savich and Sherlock and is assigned Special Agent Rome Foxe for protection. With deadly assailants in terrifying pursuit, Elizabeth and Rome soon find themselves neck deep in danger and in a race for survival. Buckle up for a nonstop, action-packed thriller from the one and only Catherine Coulter."--